Classroom observations in elementary schools with Educational Climate Assessment Tool (EduCAT): the concurrent validity with Classroom Assessment Scoring System - Wikman, Carina; Allodi, Mara Westling; Ringer, Noam (Frontiers in Education, 2024)
The classroom social–emotional climate is critical to students’ wellbeing and learning ability. In practice and research, an assessment instrument with strong validity is invaluable, providing crucial information about the classroom’s social–emotional and learning climate. This allows for a more accurate appreciation of the quality of the learning environment. A valid instrument is helpful and essential in improving the classroom climate in practice and demonstrating intervention outcomes in research. The primary aim was to evaluate the concurrent validity of the Educational Climate Assessment Tool (EduCAT)—a newly developed classroom observation instrument based on a solid theoretical framework and previous empirical research. The concurrent validity testing involved examining pairwise and multivariate canonical correlations between scores from the EduCAT scales (stimulation, improvement, structure, relationship, and influence) and scores from the Classroom Assessment Scoring System (CLASS®) administered concurrently in 30 kindergarten to third grade (K-3) classrooms in four schools in Sweden. The pairwise correlation results show that the scores of the two observation instruments have strong and moderate positive correlations, as hypothesized. The canonical correlation identifies which scales in EduCAT correlate more strongly to scales in CLASS®. The results indicate that the observations measured with EduCAT tap similar aspects of classroom climate quality to those measured with CLASS®, thereby confirming the new protocol’s concurrent validity and instilling confidence in its use.